Comparison of SARS-CoV-2 molecular results from the first two COVID-19 waves in Gauteng - Kreshalen Govender; Rendani T. Mafuyeka; Azwidowi Lukhwareni; Pieter Meyer (Southern African Journal of Infectious Diseases)
Background: Laboratory-based molecular assays return cycle threshold (Ct) values for each gene target. There is limited hyperlocal information describing the Ct, age and sex trends during the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) waves in South Africa.